Pengaruh Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Di PT Tunas Jaya - Adrinata, Rizky; Puddin, Khafi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study aims to determine, analyze, and present a discussion of research related to the influence of work motivation and work environment together on employee performance at PT. Tunas Jaya Utama, This research will be conducted at PT. Tunas Utama Jaya, In this study, the author uses quantitative research techniques. the population in this study were all employees of PT. Tunas Jaya Utama personnel totaling 50 people, the sampling technique used in this study was saturated sampling, where a population of 50 people was used as a sample, the data analysis technique used in this study was multiple linear regression analysis, the results of this study were The results of this study indicate that the Motivation variable (X1) has a positive and significant effect on Performance at α = 5%. A positive t value indicates that the motivation variable has a unidirectional relationship with Performance. The results of this study indicate that the Work Environment variable (X2) has a positive and significant effect on Performance at α = 5%. A positive t value indicates that the work environment variable has a unidirectional relationship with Performance. The results of the study indicate that the Motivation and work environment variables together (simultaneously) have a positive and significant effect on Performance